Louise Bourgeois has the day invaded the night or has the night invaded the day? - Paton, Justin 1972-; Campion, Jane 1954-; Kraus, Chris 1955-; Larratt-Smith, Philip 1979-; Webster, Jamieson (Art Gallery of New South Wales, 2023)
Day and night, love and hate, calm and chaos, conscious and unconscious. Explore Louise Bourgeois’s world of tensions and extremes in this striking new book dedicated to one of the most influential artists of the past century. Bourgeois (France/USA 1911-2010) is renowned for her fearless exploration of human relationships across a relentlessly inventive seven-decade career. Featuring more than 200 images of Bourgeois’s work, a selection of her writings and dream recordings, and new perspectives on her work by filmmaker Jane Campion and writer Chris Kraus, this book reveals the extraordinary reach and intensity of her art. From her haunting Personage sculptures of the 1940s to her iconic spiders and tough yet tender textile works of the 1990s and 2000s, Louise Bourgeois: Has the day invaded the night or has the night invaded the day? is an essential guide to this singular artist and an exploration of the polarities at the heart of her art. This publication accompanies a major exhibition of Bourgeois’s art presented at the Art Gallery of New South Wales in Sydney, Australia, and documents its dramatic presentation in the renowned post-industrial gallery called the Tank. It features further texts by exhibition curator Justin Paton, Bourgeois expert Philip LarrattSmith and psychoanalyst Jamieson Webster, and a richly illustrated chronology of the artist’s life
Curated by Justin Paton and Emily Sullivan (page [9])
Impressum: In association with the exhibition "Louise Bourgeois: Has the Day Invaded the Night or Has the Night Invaded the Day?", Art Gallery of New South Wales, Sydney, 25 November 2023 - 28 April 2024
Keywords: Bourgeois, Louise -- 1911-2010; Bourgeois, Louise / 1911-2010 / Exhibitions; Artists' writings, American; exhibition catalogs; Catalogues d'exposition; Ausstellungskatalog -- Art Gallery of New South Wales -- 25.11.2023-28.04.2024 -- Sydney; Bildband